The relationship of focus attention to the performance of high jump events in the Fosbury way - Muhsen, Ahlam Shaghati (International Journal of Psychosocial Rehabilitation, 2020)
The research aimed to develop in the digital level for every athlete and coach. To achieve this goal, psychological and physical capabilities must be invested with the help of other sciences that are related to the sciences of physical education. Since the arena and field games are considered one of the individual activities that were positively affected by the development of various sciences, including psychology and sports training. This was important, as the researcher addressed the high jump event, which needs a high level of focus and attention because it is highly jumped, exposed to a lot of external stimuli within the competition arena, including audio-visual, which relates to the level of performance of the high jump event for students. The problem lies in the fact that the teaching process or the curriculum lacks of emphasis on the personal characteristics of the student, including focusing attention, which affects the level of student performance. Also, the study aimed to know the relationship between focus attention and the level of performance of the high jump of students And the researcher assumed that there is a statistically significant correlation between attention and the level of performance of the students’ high jump effectiveness. As for the research methodology, the researcher used the descriptive approach, as the research consisted of (175) students in the College of Physical Education and Sports Science. They were randomly selected, where psychological research tests were identified (attention focus network) and a High jump test over a period of three days. The pilot study was conducted to learn about the progress and reception of the items of the test and powers of tools and devices. The results were presented, analyzed and discussed. The presentation and analysis of the results and statistical treatments were dealt with and tabulated in a set of tables. The means and standard deviations were presented and then discussed in an accurate scientific manner and supported by the sources related to the subject of the study to achieve the research objectives. The conclusions were as follows: There are non-significant differences between the performance relationship and the concentration in noise. • There are non-significant differences between the relationship of performance and concentration in calm. The researcher reached several recommendations, including: • The necessity of adopting developmental curricula and training methods that contributes to developing students’ mental capabilities. • Give great importance to attention-focused exercises for their contribution in developing basic skills for students.